Clinical Indicators of Postoperative Bleeding in Bariatric Surgery. Issue 1 (February 2018) - Fecso, Andras B.; Samuel, Timothy; Elnahas, Ahmad; Sockalingam, Sanjeev; Jackson, Timothy; Quereshy, Fayez; Okrainec, Allan
Abstract : The purpose of this study was to evaluate the relationship between patient, clinical and laboratory characteristics, and bleeding after bariatric surgery. A retrospective chart review was performed for all patients, who underwent a laparoscopic Roux-en-Y gastric bypass and laparoscopic sleeve gastrectomy at our institution between March 2012 and May 2014. In total, 788 patients were included in this study. Seventeen patients had postoperative bleeding. The demographics, comorbidities, and preoperative medications were similar between the groups. Mean postoperative hemoglobin in the bleeding group was significantly lower (94 vs. 126; P <0.001) with a larger decrease from the baseline value (−43 vs. −12; P <0.001). The mean heart rate (91 vs. 81; P <0.001) and its increase from baseline (12 vs. −0.01; P <0.001) were significantly different in the bleeding patients. Postoperative hemoglobin and heart rate were associated with bleeding but not systolic blood pressure or patient characteristics. Further research is needed to develop a robust predictive model.